Nitrogen-Doped Carbon Encapsulated Partial Zinc Stannate Nanocomposite for High-Performance Energy Storage Materials - Yu, Jiage; Liu, Zhijie; Zhang, Xian; Ding, Yu; Fu, Zhengbing; Wang, Feng (Frontiers in Chemistry, 2021)
As a bimetal oxide, partial zinc stannate (ZnSnO3) is one of the most promising next generation lithium anode materials, which has the advantages of low operating voltage, large theoretical capacity (1317mA h·g−1) and low cost. However, the shortcomings of large volume expansion and poor electrical conductivity hinder its practical application. The core-shell ZnSnO3@ nitrogen doped carbon (ZSO@NC) nanocomposite was successfully obtained by coating ZnSnO3 with polypyrrole (PPy) through in situ polymerization under ice-bath conditions. Benefiting from this unique compact structure, the shell formed by PPy can not only effectively alleviate the volume expansion effect of ZnSnO3, but also enhance the electrical conductivity, thus greatly improving the lithium storage performance. ZSO@NC can deliver a reversible capacity of a 967 mA h·g−1 at 0.1 A·g−1 after 300 cycles and 365 mA h·g−1 at 2 A·g−1 after 1000 cycles. This work may provide a new avenue for synthesis of bimetal oxide with core-shell structure for high-performance energy storage materials.